Paradoks target costing: efisiensi biaya dan inovasi di industri manufaktur - Ummi Kalsum Mutmainnah; Mukhtaruddin . (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Rapid economic shifts and Industry 4.0 have forced manufacturing firms to adopt target costing to remain competitive. However, target costing creates a strategic paradox. It demands strict cost efficiency, while radical digital innovation requires high upfront investment that often conflicts with rigid cost limits. This study analyzes whether target costing functions as an efficiency solution or a barrier to innovation. The research uses a qualitative review of 48 indexed articles from Scopus, SINTA, and Garuda. The analysis is grounded in contingency theory and strategic cost management theory. The findings show that target costing effectively eliminates non value added costs through the integration of technologies such as AI and IoT. However, when applied rigidly, it can suppress the creativity of R and D and design teams. The study concludes that target costing is not inherently an innovation barrier, but can act as a catalyst for creative problem solving. Success depends on management’s ability to balance cost discipline with flexible technology adoption. Target costing should function as a strategic navigation tool to secure long term competitive advantage without compromising product quality or the capacity for transformative innovation.